Utilization of Wireless Sensor Network to Monitor Citarum River Quality for Milkfish Cultivation in Karawang Regency - Rafi Amartya Santosa; Rizky Ariyan Qurais Shihab; Adamzah Suyuti Bakar; Joni Welman Simatupang (Fakultas Teknik, 2021)
The purpose of this research (study) is to demonstrate the superiority of the wireless sensor network (WSN) technology method over the laboratory method in monitoring the water quality of the Citarum River in Karawang. To monitor the Citarum river water quality, government of Karawang regency conducted a test by taking the sample water to the laboratory. It seems to be such a conventional method. With the results of the BOD value obtained from the DLHK data, which is 47.93 mg/L, of course it will be a problem for the development of milkfish. However, an advanced method using Wireless Sensor Network (WSN) technology seems to be an alternative. Basically, this technology can monitor the water quality in real-time using multiple parameters and help cultivators to monitor the water used in milkfish cultivation. Of course WSN technology is more efficient than waiting for laboratory results. Therefore, if this technology is applied, the data will be obtained in real time. Of course the data can be processed and monitored directly to determine the quality of the water used. In terms of cost, this technology can be built at a moderate cost compared to laboratory work.